Analysis Of Marketing Channels For Cabbage Farming In Air Duku Village, Selupu Rejang District, Rejang Lebong Regency - Indah Fitria (University of Prof. Dr. Hazairin, SH, 2022)
Water village duku is one of the villages whose residents have the main livelihood, namely cabbage farmers. In increasing production, it is necessary to pay attention to the existence of competitiveness which is a problem. This problem is also related to the development of marketing assisted by the existence of a marketing agency with efforts to increase revenue and reduce marginsmarketing.This study aims to analyze the acceptance of cabbage farming and its marketing channels in Air Duku village, Selupu Rejang district, Rejang Lebong Regency.